METHODS OF ISOLATION OF CELL FREE COMPLEXES AND CIRCULATING CELL-FREE NUCLEIC ACID - YEH, CHEN-HSIUNG (2015)
The present disclosure provides methods for the isolation of a cell free complex comprising a circulating, cell free nucleic acid component. The nucleic acid component of the complex is, at least in part, associated with cellular components, such as polypeptides and lipids. The methods of the present disclosure provide for the isolation of circulating cell free nucleic acids that are longer and less fragmented as compared to prior art methods. Furthermore, the circulating, cell free nucleic acid represent biologically relevant nucleic acid targets as the methods described selectively remove non-functional nucleic acids from the isolated material. The nucleic acid component of the isolated complexes reflects a wide spectrum of genomic representation enabling successful detection of mutations, polymorphisms, methylation status and other genomic markers for use in diagnostic and therapeutic applications. Furthermore, the additional cellular components in the cell free complexes isolated provide information regarding the proteomic and lipidomic status of the subject La présente divulgation concerne des procédés pour l'isolement d'un complexe acellulaire comprenant un composant d'acide nucléique acellulaire circulant. Le composant d'acide nucléique du complexe est, au moins en partie, associé à des composants cellulaires, tels que des polypeptides et des lipides. Les procédés selon la présente divulgation permettent l'isolement d'acides nucléiques acellulaires circulants qui sont plus longs et moins fragmentés comparativement à ceux obtenus par les procédés selon l'état de la technique. En outre, les acides nucléiques acellulaires, circulants représentent des cibles d'acides nucléiques biologiquement pertinentes dans la mesure où les procédés décrits éliminent sélectivement les acides nucléiques non fonctionnels du matériel isolé. Le composant d'acide nucléique des complexes isolés reflète un large spectre de représentations génomiques permettant la détection avec succès des mutations, des polymorphismes, de l'état de méthylation et d'autres marqueurs génomiques pouvant être utilisés dans des applications diagnostiques et thérapeutiques. En outre, les composants cellulaires supplémentaires dans les complexes acellulaires isolés fournissent des informations concernant l'état protéomique et lipidomique du sujet.